GENESIS AND COMPOSITION OF BORATES OF THE LUDWIGITE-VONSENITE SERIES IN MAGNESIAN SKARNS OF THE URALS, SIBERIA, AND THE RUSSIAN FAR EAST - Aleksandrov S.M.; Troneva M.A. (My University, 2004)
The paper considers the genesis, composition, and mineral assemblages of endogenous borates of the ludwigite-vonsenite series in magnesian skarns after dolomites, rocks simulating their composition, and calcareous skarns developed after magnesian ones at the deposits of the Urals, Siberia, and the Russian Far East. It was shown that their composition at different deposits varies from high-Mg to high-Fe varieties owing to isomorphous substitution of Mg for Fe 2+. In addition, borates show isovalent isomorphism expressed in the substitution of Fe 3+ for Al during replacement of early spinel, and for Cr during replacement of Mg-bearing Cr-spinels mainly in ultramafic rocks or early magnetite in the outer contacts of mafic intrusions. Different compensation heterovalent isomorphism is expressed in the following substitution schemes: 2Fe 3+ → (Ti 4+ + Mg) 6+ or (Sn 4+ + Mg) 6+ and 3Fe 3+ → (Sb 5+ + 2Mg) 9+ or (V 5+ + 2Mg) 9+. Thus, the composition of borates of the ludwigite-vonsenite series reflects the specific geochemical environment of the mineral formation during the skarn-ore process.